Kajian Pengelolaan Sampah Perkotaan pada Pulau Kecil Padat Penduduk di Pulau Lengkang, Kota Batam - Yosef Adicita; Mega Mutiara Sari; D. Darwin; Anshah Silmi Afifah; Nova Ulhasanah; Imelda Masni Juniaty Sianipar; Aartje Tehupeiory; Iva Yenis Septiariva; I Wayan Koko Suryawan (Jurnal Wilayah dan Lingkungan, 2022)
Marine debris is an important problem because it can directly impact the environment and public health. Good waste management is required to manage coastal waste. One of the coasts on the Indonesian border, which is experiencing an increase in waste in the ocean, is Lengkang Island. This study aims to evaluate the need for waste management facilities based on waste generation and composition. This research was carried out quantitatively and qualitatively, and the generation and composition of the waste were measured by field observations. Qualitatively, this was accomplished through a literature review. The average amount of waste in the marine waters of Lengkang Island is 19.5±3.7 kg/m2. As much as 64% of the waste thrown into the sea is plastic, and the remainder consists of paper/cardboard, rubber, and wood. Managed waste is usually illegally stockpiled, collected in temporary shelters (tempat pembuangan sampah/TPS), and then burned. These problems must be resolved by planning from source, collection, and transportation to processing at the final processing site (tempat pemrosesan akhir/TPA).